(untitled) - Kuhn, Hans (New Jersey, 2009)
The book aims to develop one of intuition on how research works by presenting many exciting original ideas and providing instructive examples that inspire thinking. Rather than always aiming for rigor, the discussion uses simplified models and approximations that can develop our intuition and guide our thinking. For thesr reasons, original research findings and current research findings are included in the examples ow as part of problems and exercises to be worked.
Keywords: Chemistry, Physical and theoretical; Hóa lý